Pengaruh Religiusitas, Pengetahuan Akuntansi Syariah dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Akuntansi Berkarir di Lembaga Keuangan Syariah (Studi Kasus Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Muhammadiyah Malang) - Ika Insiatul Iftitah; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to determine the influence of religiosity, knowledge of sharia accounting and job market considerations on the interest of accounting students to career in sharia financial institutions. Sampling in this study using purposive sampling and slovin technique. The process sed data is primary data obtained from the distribution of Google Form links and obtained by 90 respondents who have met the criteria. The method used is multiple linear regression analysis. The results showed that religiosity, knowledge of sharia accounting and job market considerations have an effect on career interest in sharia financial institutions in Accounting Students at the Islamic University of Malang and University of Muhammadiyah Malang. Keywords: Religiosity, knowledge of sharia accounting, job market consideration, and career interest.